Little House on the Prairie - Wilder, Laura Ingalls; Illustrated by Williams Garth (New York Harper Collins, 1971)
Provides activities and discussion for a group of students who all read the same book.
Including Illustrations
Keywords: Frontier and pioneer life -- Great Plains -- Families